Pendidikan Multikultural Di Sekolah Tinggi Agama Islam Brebes (Tinjauan Aspek Kognitif dan Afektif Nilai-Nilai Multikultural ) - Rohidin; Masitoh, Masitoh (Lembaga Penelitian dan Pengabdian Masyarakat STAI Brebes, 2025)
Multiculturalism can be seen as an acknowledgement of cultural pluralism. Cultural pluralism is not something that is “given” but is a process of internalizing values ​​within a community. This study provides an overview of the conceptual understanding and behavior of multicultural values ​​at the Islamic College of Brebes, Islamic Religious Education (PAI) study program. Therefore, it is important to develop multicultural education, an educational process that provides equal opportunities for all students who come from different school backgrounds. Lecturers of Multicultural Education courses must design the learning process, prepare the curriculum and evaluation design, and lecturers who have multicultural perceptions, attitudes and behaviors, so that they become a part that provides a positive contribution to the development of multicultural attitudes and behaviors of their students. This study aims to determine the ability of understanding and multicultural behavior of Islamic Religious Education (PAI) students of STAI Brebes towards the multicultural values ​​they get in lectures. This study is a qualitative study with a phenomenological approach. The primary data in this study are class A Islamic Religious Education (PAI) students of the Islamic College of Brebes. While secondary data involves designated fellow students, designated lecturers and designated academics. The results of the study show that students' understanding and behavior regarding multiculturalism values ​​are good or even very good. The values ​​understood and behavior applied by the students include tolerance values, equality values, freedom values, and discipline values